Organization of production activities of a regional coal-mining complex - Ashcheulova, O.M.; Fomichova, L.Ya.; Mamaikin, O.R.; Pochepov, V.M.; Lapko, V.V. (Физико-технические проблемы горного производства, 2021)
Objective is to propose a new approach to investment allocation in the group of coal-mining enterprises.
Methods. To solve the specified objective, a complex approach has been applied including assessment of enterprise investment attractiveness, determination of production potential, and definition of the possibility to switch to a break-even mode. The process of planning the ways to save industrial potential of coal-mining regions may be considered as the representation of multidimensional space (initial and design values) in terms of the one-dimensional (amount of investment money) one.
Findings. It has been established that the stage dealing with the development of a model for managing processes for mine unprofitability reduction should involve consideration of 8-10 factorial features, which may determine the formation of economic potential, taking into account peculiarities of the remaining deposits and their quality, as the integral assessment of mine potential in terms of both state and non-state investments. The formulated objective means selection of the minimum number of factors, which would reflect in the most adequate way the internal potential of a mine expressed by economic added value – as a consequence of interaction of factors of coal mine economic activities in specific mining, geological, and technological conditions.
Originality of the research is in the fact that it is expedient to use an indicator of economic reliability, which synthesizes the capacity of links, economic level of technical and economic indicators, and the amount of remaining deposits, as a complex component of the level of an unprofitable mine. The mentioned indicators determine the residual life of the mine. Their physical content is not identical; and it is the fact that helps (in terms of their joint use) obtain more complete estimate than when using any single indicator.
Practical implications. Practical significance includes actual assessment of the state of Donbas coal enterprises and determination of marginal break-even indicators, which has made it possible to elaborate recommendations for attracting financial resources. Мета. Запропонувати новий підхід щодо механізму оцінки доцільності підтримки виробничих потужностей збиткових шахт Донецької та Дніпропетровської областей.
Методика. Для вирішення поставленої проблеми застосовано комплексний підхід, який включає оцінку інвестиційної привабливості підприємства, визначення виробничого потенціалу, визначення можливості переходу на беззбитковий режим. Процес планування шляхів збереження промислового потенціалу вуглепромислових регіонів може розглядатися як відображення багатовимірного простору (початкових і проектних величин) в одновимірний (суму інвестиційних коштів).
Результати. Встановлено, що на стадії побудови моделі управління процесами зниження збитковості шахти необхідно розглянути 8-10 факторних ознак, які можуть визначати формування економічного потенціалу з урахуванням особливостей залягання запасів, що залишилися та їх якості, як інтегральної оцінки потенціалу шахти в частині сприйняття інвестицій (державних та недержавних). Поставлена задача зводиться до відбору найменшого числа факторів, які б найбільш адекватно відображали внутрішній потенціал шахти у виразі економічної доданої вартості – як наслідок взаємодії факторів економічної діяльності вугільної шахти в конкретних гірничо-геологічних і технологічних умовах.
Наукова новизна полягає в тому, що в якості комплексної складової рівня стану збиткової шахти доцільно використати показник економічної надійності, який синтезує пропускну здатність ланок, економічний рівень техніко-економічних показників і обсяг запасів, що залишилися. Останні визначають залишковий термін служби шахти, фізичний зміст запропонованих показників неоднаковий, і саме ця обставина дозволяє при їх спільному використанні отримати більш повну, ніж при використанні якого-небудь одного показника, оцінку.
Практична значимість полягає у проведенні фактичної оцінки стану вугільних підприємств Донбасу та визначенні граничних показників беззбитковості, що дозволило сформувати рекомендації по залученню об’ємів фінансових ресурсів. Цель. Предложить новый подход к распределению инвестиций в группе предприятий по добыче угля.
Методы. Для решения поставленной проблемы применен комплексный подход, включающий оценку инвестиционной привлекательности предприятия, определение производственного потенциала, определения возможности перехода на безубыточный режим. Процесс планирования путей сохранения промышленного потенциала углепромышленных регионов может рассматриваться как отражение многомерного пространства (начальных и проектных величин) в одномерный (сумму инвестиционных средств).
Результаты. Установлено, что на стадии построения модели управления процессами снижения убыточности шахты необходимо рассмотреть
8-10 факторных признаков, которые могут определять формирование экономического потенциала с учетом особенностей залегания оставшихся запасов и их качества, как интегральной оценки потенциала шахты в части восприятия инвестиций (государственных и негосударственных). Поставленная задача сводится к отбору наименьшего числа факторов, которые наиболее адекватно отражают внутренний потенциал шахты в выражении экономической добавленной стоимости – как следствие взаимодействия факторов экономической деятельности угольной шахты в конкретных горно-геологических и технологических условиях.
Научная новизна заключается в том, что в качестве комплексной составляющей уровня состояния убыточной шахты целесообразно использовать показатель экономической надежности, который синтезирует пропускную способность звеньев, экономический уровень технико-экономических показателей и объем оставшихся запасов. Последние определяют остаточный срок службы шахты, физический смысл предложенных показателей неодинаков, и именно это обстоятельство позволяет при их совместном использовании получить более полную, чем при использовании какого-либо одного показателя, оценку.
Практическая значимость заключается в проведении фактической оценки состояния угольных предприятий Донбасса и определении предельных показателей безубыточности, что позволило сформировать рекомендации по привлечению объемов финансовых ресурсов.